Empowering Mothers: The Critical Role of Knowledge and Positive Attitudes in Shaping Prenatal Nutritional Choices - Hasritawati; Sri Wahyuni; Barirah Madeni (Archives of The Medicine and Case Reports, 2025)
Optimal prenatal nutrition is foundational for positive maternal and fetal health, significantly impacting lifelong well-being. A pregnant woman's nutritional knowledge and attitudes are pivotal, modifiable determinants influencing her dietary choices. Inadequate knowledge or negative attitudes can precipitate suboptimal nutritional intake, thereby elevating risks for adverse outcomes such as maternal morbidity, intrauterine growth restriction, and developmental issues in the child. This study aimed to comprehensively explore the nexus between pregnant women's nutritional knowledge, their attitudes concerning gestational nutritional needs, and the consequent influence on their prenatal dietary practices within a distinct rural Indonesian community. This descriptive analytical study adopted a cross-sectional design, conducted in Desa Bale Redelong, Kecamatan Bukit, Kabupaten Bener Meriah, Aceh, Indonesia. The entire population of 60 pregnant women accessing local midwifery antenatal services was included via total population sampling. A structured, pre-tested questionnaire was administered to collect data on socio-demographic characteristics, nutritional knowledge, attitudes towards nutritional needs (independent variables), and self-reported nutritional practices (dependent variable). Data analysis encompassed descriptive statistics, Chi-Square (χ²) tests for bivariate associations, and a multivariate logistic regression to identify key predictors of good nutritional practices, with statistical significance set at p < 0.05. Baseline data (n=60) depicted a cohort primarily aged 20-35 years (70.0%), with secondary education (55.0%). Nutritional knowledge was 'good' in 33.33%, 'sufficient' in 40.0%, and 'poor' in 26.67% of participants. Positive attitudes towards nutrition were held by 63.33%, while 36.67% exhibited negative attitudes. Bivariate analysis revealed significant positive associations between higher nutritional knowledge (χ²=10.833, p=0.001) and positive attitudes (χ²=6.136, p=0.013) with good nutritional practices. Multivariate logistic regression indicated that 'good' knowledge (Adjusted Odds Ratio [aOR] = 3.8; 95% CI: 1.5-9.6; p=0.005) and 'positive' attitudes (aOR = 2.9; 95% CI: 1.1-7.8; p=0.030) were significant independent predictors of good nutritional practices, after controlling for maternal age and education. In conclusion, this study underscores the critical and independent roles of both robust nutritional knowledge and positive attitudes in shaping the prenatal dietary choices of pregnant women in the investigated community. Even when accounting for socio-demographic variables, enhanced knowledge and favorable attitudes significantly predicted improved nutritional practices. These insights strongly advocate for multifaceted, culturally-sensitive public health interventions designed not only to impart factual information but also to cultivate empowering attitudes, thereby enabling pregnant women to make informed, health-promoting nutritional decisions for optimal maternal and child outcomes.